Avaliação do risco de inibidor associado ao uso de concentrado de fator VIII recombinante em pacientes com hemofilia A previamente tratados e previamente não tratados no Brasil (BraSIL-rFVIII: Brazilian Study Of Inhibitor Linked To Recombinant Factor VIII) : Assessment of inhibitor risk associated with the use of recombinant factor VIII concentrate in previously treated and previously untreated patients with hemophilia A in Brazil (BraSIL-rFVIII: Brazilian Study Of Inhibitor Linked To Recombinant Factor VIII) - Prezotti, Alessandra Nunes Loureiro, 1973- (2022)
Orientador: Margareth Castro Ozelo